Cytological Analysis Of Body Fluids In Conventional Smear And Cell Block Technique-Study Of 120 Cases - POORANA PRIYA.P (International Journal of Pharma and Bio Sciences, 2015)
The cytological study of body fluids is an important diagnostic modality. It helps in finding out the etiology as well as the prognosis of the disease process. In our study, a total of 120 fluid samples were examined for conventional cytological smear and cellblock method. Out of 120 fluids, 58 were peritoneal fluid, 55 were pleural fluid, 4 were synovial and 3 pericardial fluid. Overall morphology, cellularity, architecture, cytoplasmic and nuclear details were studied in both conventional smear and cell block technique. We found statistically significant difference between both the techniques. The utility of cell block method in cytodiagnosis of malignant effusions was significant in our study.